Tantangan Guru dalam Mendampingi Anak ADHD (Studi KASUS di kelas 3 SDN Cipondok) - Khoirunnisa, Nida; Juherna, Erna; Aulia, Nayla Ainaika; Priatna, Agung; Adelia, Bunga Eka; Hidayat, Pulan Putri; Zakiah, Ulpa; Salsabila, Mahandari Desvita; Ningrum, Reza Maisa (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The presence of students with Attention Deficit Hyperactivity Disorder (ADHD) in mainstream classrooms requires teachers to implement more dynamic classroom management strategies. This study explores the real-world challenges faced by a third-grade teacher at SDN Cipondok in guiding an ADHD student who exhibits hyperactive behavior and significant difficulty maintaining focus. Using a descriptive qualitative approach, data were gathered through classroom observations, in-depth interviews with the teacher, and an analysis of documents related to the student's development. The findings reveal that the primary obstacle lies in the teacher's dual workload, caused by the absence of a shadow teacher and a lack of specialized learning media to engage the student's attention. Furthermore, environmental factors and a lack of intensive collaboration with parents hinder the optimization of the learning process. This study suggests the critical need for specialized training for general classroom teachers to better manage the diverse needs of students in an inclusive school setting.